Factors Associated With Rape Case Attrition in the South African Criminal Justice System: a National Cross-Sectional Study - Machisa, Mercilene (The British journal of criminology, 2023)
The attrition of rape cases within the criminal justice system is driven by different factors. We aimed to describe the patterns of rape case attrition and associated factors in South Africa. We analysed a national sample of 3,952 cases reported in 2012. We found that 35 per cent of cases were closed by police, 31 per cent were declined by the prosecutors, 16 per cent were enrolled but later struck off the roll, 19 per cent went on trial and 9 per cent were finalised with conviction. Aggravating circumstances, availability of forensic evidence and success at perpetrator arrests were key for case progression and increased likelihood of convictions. Thorough police investigations and continual training which addresses negative gender or other rape stereotyping are critical to ensure rape convictions.